Sclerodermatomyositis - Febyani, M; D, H Purbo; Hamijoyo, Laniyati; Sutedja, E; Suwarsa, O (Indonesian Journal of Rheumatology, 2011)
The classification of rheumatic diseases is still challenging due to several reasons. First, those diseases have several differential clinical features, which giving overlap symptoms. Second, the etiopathogenesis of those diseases remains elusive.Diagnosis of overlap syndrome is made when there are more than one well-defined connective tissue diseases in one patient, which may develop simultaneously or sequentially.1,2 The prevalence of overlap syndrome among autoimmune diseases is25%.2 The term sclerodermatomyositis or scleromyositisis is used to describe an overlap syndrome in patients with scleroderma and dermatomyositis/polymyositis (DM/PM).2,3,4 Sclerodermatomyositis usually affects adults, and it is rarely found in children.4 The clinical features of this syndrome are myalgia or myositis, arthralgia, scleroderma-like skin changes, Raynaudâs phenomenon (RP),2,3 interstitial lung disease, calcinosis,3 mask-like facies, dysphagia or esophageal dysmotility,4 as well as the presence of specific antibody Pm/Scl.2 Skin manifestations as the part of dermatomyositis include periorbital erythema and Gottronâs papules.3 We report this case due to its very rare occurrence. According to medical records in the Department of Dermatology as well as Rheumatology at Hasan Sadikin Hospital, Bandung, this is the first case recorded in the last 10 years.